(untitled) (SP Swag: Sudur Paschim Wisdom of Academic Gentry Journal, 2024)
This editorial delves into the impact of agricultural financing policies in Nepal, highlighting their role in enhancing farmers’ access to credit and improving agricultural productivity. Drawing on studies by various researchers, it explores the positive outcomes of initiatives like the Agricultural Credit Guarantee Scheme (ACGS) and Prime Minister Agriculture Modernization Project (PMAMP), which have led to increased credit disbursements and adoption of modern agricultural practices. Despite these successes, challenges such as limited collateral, high-interest rates, and financial literacy gaps persist, underscoring the need for further reforms. The editorial also discusses opportunities for improvement, including innovative financing models and enhanced rural infrastructure, in alignment with Nepal’s agricultural perspective plan and monetary policies. Overall, it emphasizes the crucial link between agricultural financing, economic development, food security, and poverty reduction in Nepal. DOI: https://doi.org/10.69476/sdpr.2024.v01i01.001